Yoga for the rest of us. Back care basics [videorecording (DVD)] - Baynard, John (WGBH Boston Video, 2007)
Shows the right exercises and yoga poses to protect your back and improve your posture. Includes a bonus segment for restoring poses using the help of gravity.